Camundongos infectados experimentalmente com Trypanosoma cruzi: efeito da doença de chagas sobre as enzimas purinérgicas e testes de um novo protocolo tripanocida - Carmo, Guilherme Machado do (2018)
Chagas disease is a zoonosis caused by Trypanosoma cruzi. It occurs primarily in Latin America, where it causes serious health problems for about 7 million people in endemic regions. Considering that Chagas disease currently few effective treatments, and those that exist carry several side effects, new alternatives for treatment should be evaluated. Therefore, the objective of this study was to evaluate the efficacy of cordycepin (an adenosine analogue) and pentostatin (an inhibitor of the enzyme adenosine deaminase) in mice experimentally-infected with T. cruzi, and also to verify if the purinergic system is affected and has a role in the pathogenesis of Chagas disease. We did this because nucleosides and nucleotides in the purinergic cascade are involved in the pathophysiology of various parasitic infections. The study design was divided into four experimental protocols. In the experimental protocol I, the animals were divided into two groups (n = 6): control group (not infected with T. cruzi), and infected group (infected with T. cruzi). We then investigated the effect of purinergic enzymes on platelets, lymphocytes, and hearts in experimentally-infected mice infected with T. cruzi (strain Y). We observed increased activity of E-NTPDase (ATP and ADP substrates) and E-ADA in lymphocytes of T. cruzi-infected mice (P <.01). We observed inflammatory infiltrates in the heart, as well as multiple pseudocysts containing amastigotes. However, NTPDase activity did not change in the T. cruzi-infected group, but there was a reduction in the activity of 5'-nucleotidase (P <.001) and an increase in ADA activity in infected mice (P <.05). Activity of E-NTPDase (ATP and ADP substrates), E-5'nucleotidase and E-ADA in platelets increased significantly (P <.05) in mice infected with T. cruzi. In the experimental protocol II, the animals were divided into 10 groups with six animals (five control groups and five infected groups), in which the animals of the infected groups were inoculated with 104 triposmastigotes of strain Y. In this experimental protocol, we evaluated the efficacy of treatment with cordycepin and pentostatin (isolated or in combination), as well as the effect of treatment on purinergic enzymes in vivo. From this design we obtained the curative ineffectiveness of the experimental protocol, despite having reduced parasitemia. We also found that serum NTPDase activity (ATP; P <.001, ADP; P <.05) and ADA (P <.001) were higher in untreated T. cruzi-infected mice. However, mice treated with a combination of 3'-deoxyadenosine and deoxycoformycin were able to modulate NTPDase activity (ATP and ADP substrate) and ADA, preventing the increase in activity in infected animals (i.e., to activity levels similar to those of healthy animals). The activity of 5'-nucleotidase significantly decreased (P <.01) in untreated infected animals, but treatment prevented the reduction of 5'-nucleotidase activity. In experimental protocol III, the animals were divided into five groups of six animals each (one control group and four infected groups), in which the animals of the infected groups were inoculated with triphosmastigotes of the benznidazole-resistant strain (Colombian strain). In protocol III, we evaluated the efficacy of the treatment with cordycepin and pentostatin (alone or in combination). In this protocol, we also performed in vitro tests to evaluate the efficacy of the compounds against T. cruzi. In this experiment, the results were similar to those of protocol II, i.e., ineffectiveness of treatments in mice infected with T. cruzi. In the in vitro experiment, we observed a significant reduction (P <.001) of epimastigotes and trypomastigotes in groups treated with cordycepin and pentostatin (alone or combined) at all doses tested. For epimastigotes and trypomastigotes the lethal doses of the association of cordycepin with pentostatin capable of killing 50% (DL50) of parasites were 0.068 mg/mL and 0.027 mg/mL, respectively. In experimental protocol IV, the animals were divided into two groups (n = 6): control group (not infected with T. cruzi) and infected group (infected with T. cruzi). The animals in the infected group were inoculated with 104 triphosmastigotes from the Colombian strain, and we evaluated the effects of the infection on serum purine concentrations. In this protocol, we observed a significant increase (P <.05) in serum levels of ATP, (ADP), adenosine (ADO), inosine (INO) and uric acid (URIC) in infected animals. By contrast, the levels of adenosine monophosphate (AMP) and xanthine (XAN) reduced significantly (P <.05). Therefore, we can conclude in general that T. cruzi infection alters purinergic system enzymes, as well as purine levels, demonstrating that they are directly related to the pathophysiology of Chagas disease. The therapeutic protocol, at the dose used, should not be recommended for the treatment of Chagas disease, since it had no curative efficacy.